Adipose tissue dysfunction as a central mechanism leading to dysmetabolic obesity triggered by chronic exposure to p,p’-DDE - Pestana, Diogo (2019)
Endocrine-disrupting chemicals such as p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE), are bioaccumulated in the adipose tissue (AT) and have been implicated in the obesity and diabetes epidemic. Thus, it is hypothesized that p,p'-DDE exposure could aggravate the harm of an obesogenic context. We explored the effects of 12 weeks exposure in male Wistar rats' metabolism and AT biology, assessing a range of metabolic, biochemical and histological parameters. p,p'-DDE -treatment exacerbated several of the metabolic syndrome-accompanying features induced by high-fat diet (HF), such as dyslipidaemia, glucose intolerance and hypertension. A transcriptome analysis comparing mesenteric visceral AT (vAT) of HF and HF/DDE groups revealed a decrease in expression of nervous system and tissue development-related genes, with special relevance for the neuropeptide galanin that also revealed DNA methylation changes at its promoter region. Additionally, we observed an increase in transcription of dipeptidylpeptidase 4, as well as a plasmatic increase of the pro-inflammatory cytokine IL-1β. Our results suggest that p,p'-DDE impairs vAT normal function and effectively decreases the dynamic response to energy surplus. We conclude that p,p'-DDE does not merely accumulate in fat, but may contribute significantly to the development of metabolic dysfunction and inflammation. Our findings reinforce their recognition as metabolism disrupting chemicals, even in non-obesogenic contexts.